ANALISIS KETERAMPILAN BERBICARA SISWA MELALUI PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW PADA PEMBELAJARAN BAHASA INDONESIA KELAS V A SD NEGERI MANNURUKI - Sarmila, Mila; Munirah; Ayu Andhira, Desy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low speaking skills of students in Indonesian language learning, especially in the aspects of pronunciation, sentence structure, content, and speaking fluency. The study aimed to analyze students’ speaking skills through the implementation of the Cooperative Learning Jigsaw type model in class V A of SD Negeri Mannuruki. This study used a qualitative approach with a descriptive qualitative design. The subjects of the study consisted of the homeroom teacher and 32 students of class V A. Data were collected through tests, observations, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Cooperative Learning Jigsaw type model had a positive impact on students’ speaking skills. Students became more active, confident in expressing opinions, and able to cooperate in groups. Improvement in speaking skills was seen in clearer pronunciation, better sentence structure, relevant speaking content, and increased fluency. Therefore, the Cooperative Learning Jigsaw type model can be used as an effective alternative learning model to improve elementary school students’ speaking skills.